2019
DOI: 10.1002/mar.21202
|View full text |Cite
|
Sign up to set email alerts
|

Assessing experiential augmentation of the environment in the valuation of wine: Evidence from an economic experiment in Mt. Etna, Italy

Abstract: In this study, we conducted an experimental auction to determine the impacts that "experiential augmentation," a phenomenon in which a physical location impacts decision-making, has on consumers' willingness to pay (WTP) for wine. The experiment elicited subjects' valuation under experiential augmentation conditions for three types of wine grown in the Mt. Etna area in Sicily, Italy. Our findings indicate that experiential augmentation increased consumers' WTP for wine. Our results suggest that experiential ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…(2019).Impact of music: De Luca et al. (2019); Hsu and Chen (2019).Other kinds of interaction (culture, location): Pappalardo et al. (2019); Velikova et al.…”
Section: Synthesis Of the Resultsmentioning
confidence: 99%
“…(2019).Impact of music: De Luca et al. (2019); Hsu and Chen (2019).Other kinds of interaction (culture, location): Pappalardo et al. (2019); Velikova et al.…”
Section: Synthesis Of the Resultsmentioning
confidence: 99%
“…In these environments, consumers are not just purchasing wine but a product bundled with an experience, and per-bottle margins tend to be higher (Barber, Donovan, and Dodd, 2008). Research has shown that the location/environment in which experiences occur can improve quality perceptions and WTP, and these effects are long-lasting (Pappalardo et al, 2019). Tourism activities, however, tend to be seasonal, so the potential to increase volume is limited.…”
Section: Discussion and Policy Recommendationsmentioning
confidence: 99%
“…Following similar wine studies (Danner et al , 2017; Pappalardo et al , 2019; Vecchio et al , 2019), the sample size was set at 150 participants. Respondents were recruited by an external consumer association, in summer 2018, informing they would participate in a marketing research survey at the University campus that would last approximately an hour.…”
Section: Methodsmentioning
confidence: 99%